Antioxidant properties of novel curcumin analogues: A combined experimental and computational study. Issue 1 (19th December 2020) - Slavova‐Kazakova, Adriana; Angelova, Silvia; Fabbri, Davide; Antonietta Dettori, Maria; Kancheva, Vessela D.; Delogu, Giovanna
Abstract: The multi‐target activity of curcumin makes it a promising pharmacological lead for structural modifications focused on the preparation of new better therapeutics with improved bioavailability. A possible modification is to "decompose" the parent curcumin structure into constituent units and to build up curcumin analogues with biphenyl structural moiety. The antioxidant properties of the so‐called "monomers" (m1–m3) and "dimers" (d1–d3) are studied experimentally and computationally. Their protective effects as chain‐breaking antioxidants are investigated for the individual compounds and in binary/ternary compositions with α‐tocopherol (TOH) and ascorbyl palmitate (AscPH). All monomers manifest significant synergism up to 70% in mixtures with TOH. Synergistic effects are found for the ternary compositions of monomeric analogues upon addition to the binary mixture of standard antioxidants (TOH + AscPH). Dimers with biphenyl skeleton manifest a lower potential in compositions under lipid oxidation conditions. DFT computations provide a detailed insight into the structure and antiradical properties of the curcumin analogues and standard antioxidants. Practical applications: Bioactive compounds in the diet play a crucial role in the prevention of numerous diseases in whose pathogenesis oxidative stress is well known to be involved. Therefore, enhancement of the antioxidant status of the biological target is often helpful. Two of the monomers studied are considered leading agents in the treatment or prophylaxis of smooth muscle disorders and are useful in the maintenance of the normal gut function‐ as a calmative for the gut and to ease upset stomach. We hypothesized that the presence of a biphenyl scaffold in the parent molecular structure can enhance the biological activity. Equimolar mixtures of TOH with studied compounds have potential application in food chemistry and medicine. A composition comprising the active agent and additional components (strong conventional antioxidants) may be administered in foodstuffs, as a food supplement, beverage supplement, or as a pharmaceutical composition. Abstract : The multi‐target activity of curcumin makes it a promising pharmacological lead for structural modifications focused on the preparation of new therapeutics with improved bioavailability. A possible modification is to "decompose" the parent curcumin structure into constituent units and to build up curcumin analogues with biphenyl structural moiety. Their antioxidant compositions with DL‐α‐tocopherol and ascorbyl palmitate are able to ensure an enhanced protective effect on the lipid substrates and have the necessary qualities to become useful in medicine and agriculture.